2017
DOI: 10.1007/s00018-017-2632-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mutation in the ALS/FTD gene, CCNF, causes elevated Lys48-linked ubiquitylation and defective autophagy

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are fatal neurodegenerative disorders that have common molecular and pathogenic characteristics, such as aberrant accumulation and ubiquitylation of TDP-43; however, the mechanisms that drive this process remain poorly understood. We have recently identified CCNF mutations in familial and sporadic ALS and FTD patients. CCNF encodes cyclin F, a component of an E3 ubiquitin-protein ligase (SCF) complex that is responsible for ubiquitylating pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…Regardless of the cause/effect relationship between these aggregated proteins and disease, one hypothesis suggests the mechanism(s) involved in regulating aggregates, e.g., protein turnover/autophagy, might also become compromised in aggregate bearing cells and in turn contribute to disease. Consistent with this notion are numerous studies linking several important autophagy and proteostasis genes to ALS: Sequestosome 1 (SQSTM1)/ p62, Optineurin (OPTN), TBK1, Ubiquilin 2 (UBQLN2), Valosin Containing Protein (VCP), and cyclin F (CCNF) [53][54][55][56][57][58][59][60] (Table 1). While the link between SOD1, TDP-43, and FUS with autophagy-related genes may be the ability to maintain cellular homeostasis, it remains unclear why this pathology affects only a subpopulation of MNs.…”
Section: Looking At Als/ftld Through a Genetic Perspectivementioning
confidence: 62%
“…Regardless of the cause/effect relationship between these aggregated proteins and disease, one hypothesis suggests the mechanism(s) involved in regulating aggregates, e.g., protein turnover/autophagy, might also become compromised in aggregate bearing cells and in turn contribute to disease. Consistent with this notion are numerous studies linking several important autophagy and proteostasis genes to ALS: Sequestosome 1 (SQSTM1)/ p62, Optineurin (OPTN), TBK1, Ubiquilin 2 (UBQLN2), Valosin Containing Protein (VCP), and cyclin F (CCNF) [53][54][55][56][57][58][59][60] (Table 1). While the link between SOD1, TDP-43, and FUS with autophagy-related genes may be the ability to maintain cellular homeostasis, it remains unclear why this pathology affects only a subpopulation of MNs.…”
Section: Looking At Als/ftld Through a Genetic Perspectivementioning
confidence: 62%
“…CCNF catalyzes the transfer of activated ubiquitin to targeted proteins, which are then degraded via the ubiquitin-proteasome system (UPS) [62]. The CCNF mutant, Ser621Gly, impaired this degradation system by disrupting the Lys48-specific ubiquitylation, leading to accumulation of ubiquitinated proteins, including RRM2 and TDP-43, in neuronal cells (Figure 1 and Box 2) [15,63]. Comparable with TBK1, CCNF interacts with SQSTM1, an autophagic receptor that recognizes and transfers ubiquitinated proteins for autophagic degradation [63].…”
Section: Ccnfmentioning
confidence: 99%
“…The CCNF mutant, Ser621Gly, impaired this degradation system by disrupting the Lys48-specific ubiquitylation, leading to accumulation of ubiquitinated proteins, including RRM2 and TDP-43, in neuronal cells (Figure 1 and Box 2) [15,63]. Comparable with TBK1, CCNF interacts with SQSTM1, an autophagic receptor that recognizes and transfers ubiquitinated proteins for autophagic degradation [63]. In a recent study in zebrafish, disruption of axonal outgrowth by the mutant Ser621Gly CCNF was observed, suggesting a toxic gain-offunction mechanism for CCNF mutations in ALS patients [64].…”
Section: Ccnfmentioning
confidence: 99%
“…Cyclin F, encoded by CCNF, is one of the components of an E3 ubiquitin-protein ligase complex also known as SCF CyclinF (Skp1-Cul1-F-box E3 ubiquitin ligase complex) (Galper et al, 2017). Mutation of CCNF in neuronal cells causes errors in ubiquitination leading to ubiquitinated protein accumulation of SCF CyclinF and TDP-43 as well as impairment of autophagosome-lysosome fusion (Williams et al, 2016;Lee et al, 2018). Recently, a CCNF mutation in a zebrafish model has been shown to have disrupted axonal outgrowth (Galper et al, 2017;Hogan et al, 2017).…”
Section: Cyclin F (Ccnf)mentioning
confidence: 99%